Western Political Thought : From the Ancient Greeks to Modern Times, 2nd Edition by Pearson, 2nd Edition - Jha, Shefali (Pearson, 2018)
Western Political Thought, 2E is an attempt to include in its reach the political ideas of some of the more recent thinkers. These thinkers certainly draw on the classics of western political thought like the writings of Marx, Rousseau, Locke and Aristotle; however, they also extend our understanding of the political thought in several ways. The latest edition gives a comprehensive account of the thread of political thought that stretches from the ancient Greeks to modern times. Analysing political philosophies chronologically, this book offers valuable insights into the political structures of societies across the ages and presents a wide perspective on the various social and political ideologies.